2019
DOI: 10.1111/ajd.13199
|View full text |Cite
|
Sign up to set email alerts
|

A clinical, pathological and immunohistochemical series of 9 cases of primary cutaneous apocrine carcinomas of the head and neck

Abstract: Background/Objectives: Primary cutaneous apocrine carcinoma is a rare malignant adnexal skin tumour that can recur locally, spread to regional lymph nodes and metastatize to visceral organs. Wide dissemination and death from disease are much less common. The axilla is the most common site of presentation. It is infrequently reported in the head and neck region.Methods: All cases diagnosed as primary cutaneous apocrine carcinoma of the head and neck were retrospectively collected from the archives of the Divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Lee et al reported a case of a patient with metastatic porocarcinoma who achieved a clinical and radiological response when treated with pembrolizumab [ 52 ]. For hidradenocarcinoma, apocrine carcinoma, and signet-ring call/histiocytoid carcinoma, HER2 inhibitors or selective estrogen receptor modulators may be administered [ 53 , 54 , 55 , 56 , 57 , 58 ]. Additionally, anti-androgenic therapy is beneficial for patients with signet-ring call/histiocytoid carcinoma [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported a case of a patient with metastatic porocarcinoma who achieved a clinical and radiological response when treated with pembrolizumab [ 52 ]. For hidradenocarcinoma, apocrine carcinoma, and signet-ring call/histiocytoid carcinoma, HER2 inhibitors or selective estrogen receptor modulators may be administered [ 53 , 54 , 55 , 56 , 57 , 58 ]. Additionally, anti-androgenic therapy is beneficial for patients with signet-ring call/histiocytoid carcinoma [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few adnexal malignancies show a favorable prognosis, and no cases of recurrent or metastatic disease were reported [183,189,193,195]. [151,[154][155][156]321] A: 45-70 [151] Squamoid eccrine ductal carcinoma R ND [162,322] ND [161,162,322] Syringocystadenocarcinoma papilliferum R LD [170,172] LD [170][171][172] Secretory carcinoma R ND [183] ND [183] Cribriform carcinoma R ND [189,190,193] ND [189,193] Signet-ring cell/histiocytoid carcinoma R NA, A-conventional and targeted therapy (HER2 inhibitors, tamoxifen, anti-androgen) [23,197,199,204] NA, A [24,197,199,203,204] Hidrocystoma/cystadenoma R ND ND In a recent single-institution experience report, the median overall survival (OS) was 158 months (95% CI, . Age > 60 years was an unfavorable predictor of OS (HR 12.9, p < 0.0008) and recurrence-free survival (RFS) (HR 12.53, p < 0.0003).…”
Section: Discussionmentioning
confidence: 99%
“…Morabito et al reported a case of recurrent disease previously treated with surgery, radiotherapy, and chemotherapy (Al-Saraff schedule). The patient responded to a second-line systemic chemotherapy regimen consisting of methotrexate and bleomycin [ 155 ]. HER2 inhibitors (tanstuzumab) are also used [ 156 , 157 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%
“…In context of the primary diagnosis of the patient’s tumor as a metastatic cutaneous apocrine sweat gland carcinoma (CAC), the immunohistochemistry profile of the tumor tissue had been AR + . ER + , PR - , HER2 - , CK7 + [ 4 ]. GCDFP15 - and mammaglobin - (SCGB2A2) [ 5 ] with Ki67 index of 40%.…”
Section: Methodsmentioning
confidence: 99%
“…Metastatic cutaneous apocrine gland carcinoma (CAC) is an extreme rare malignancy arising from a sweat gland with < 30 reported cases in the literature [ 1 3 ]. Majority of these reported cases are derived from the axilla with only a few cases originating from other regions of the integumentary system [ 4 ]. The tumorigenesis of these rare cancers is largely unclear, but histologically cutaneous apocrine gland carcinomas mimic metastatic apocrine breast cancer or apocrine carcinomas arising in ectopic breast tissue [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%